Molecular processes leading to aberrant androgen receptor signaling and castration resistance in prostate cancer. Issue 5 (September 2010) - Hu, Rong; Denmeade, Samuel R; Luo, Jun
Hormone therapies targeting androgen receptor signaling are the mainstay of treatment for patients with advanced prostate cancer. The length of clinical remission induced by hormone therapies varies substantially among treated patients. Why some patients progress rapidly after treatment while others benefit with prolonged remission is a question that remains unsolved. The androgen receptor signaling pathway is the key molecular determinant of castration resistance, and a key target for prostate cancer drug design. Recent advances in characterizing molecular processes leading to the development of castration-resistant prostate cancer, including the discovery of multiple androgen receptor splicing variants, offer opportunities for rational development of new clinical tools or approaches to predict, monitor or control/prevent prostate cancer progression in the castrate setting.